MicroRNA-125b-5p Correlates With Prognosis and Lung Adenocarcinoma Progression - Tang, Lin; Yuan, Yixiao; Zhai, Haoqing; Wang, Juan; Zhang, Dahang; Liang, Huasu; Shi, Yulin; Duan, Lincan; Jiang, Xiulin (Frontiers in Molecular Biosciences, 2022)
A growing number of studies have focused on investigating microRNAs as crucial regulators in the progression of multiple cancer types. Nevertheless, the biological effects and immunological role of miR-125b-5p in non-small cell lung cancer (NSCLC) have not been determined. The present study aimed to examine the function of miR-125b-5p on the cell proliferation and the outcomes of NSCLC patients. We utilized the diverse public databases analysis the expression, prognosis, diagnostic value and immune role of miR-125b-5p in non-small cell lung cancer. The growth curve, colony formation, flow cytometry, transwell and invasion assays were utilized to determine the function of miR-125b-5p in NSCLC progression. In this study, we found that miR-125b-5p was decreased in NSCLC and correlated with poor prognosis. Pathways analyses revealed that miR-125b-5p was mainly involved in cell proliferation and immune regulation. Moreover, in vitro experiments indicated that over-expression of miR-125b-5p significantly inhibits cell proliferation, migration, invasion and induced cell apoptosis of NSCLC. Finally, we discovered that miR-125b-5p is correlated with immune cell infiltration. In summary, these results demonstrated that miR-125b-5p serve as a prognostic marker and a therapeutic target for NSCLC.